Non-thermal treatments for the control of endogenous formaldehyde from Auricularia auricula and their effects on its nutritional characteristics. (December 2022) - Wang, Xingnan; Yang, Siqi; Li, Hongcai; Ren, Yichen; Wang, Yaqin; Huang, Jintao; Wang, Zhouli; Yue, Tianli; Gao, Zhenpeng
Abstract: To control endogenous formaldehyde (EFA) from Auricularia auricula and preserve its nutritional properties, we selected various non-thermal treatments and evaluated their effects on the removal of EFA, inhibition of γ-glutamyl transpeptidase and l -cysteine sulfoxide lyase activities, and bioactive ingredients (i.e., principal nutrients, including vitamins and taste substances). The results showed that single and co-non-thermal treatments (US-EW, IPL-EW) reduced the EFA content of A. auricula to varying degrees. Correlation and principal component analyses showed that synergistic treatment with ultrasound and electrolyzed water (US-EW) significantly reduced EFA (removal rate = 40.54%), with relatively small losses of other chemical components. The second best was treatment with intense pulsed light and electrolyzed water (IPL-EW) (removal rate = 36.27%). We constructed and validated a kinetic model for EFA removal using the US–EW treatment, and fitted a second-order kinetic equation. The optimal process parameters were as follows: ultrasound (US) frequency: 50 kHz, US power: 100 W, and available chlorine concentration of EW: 35 mg/L. These results were verified and can serve as a reliable technical reference to improve safety during the processing and preservation of edible fungi. Highlights: US-EW has the highest removal rate of EFA (40.54%). The removal of EFA via US-EW confirmed the second-order reaction kinetic. The optimal processing parameters for US-EW removal of EFA have been obtained. US-EW causes the least loss in nutritional quality of A. auricula .